The Socio-Ecological Dynamics of Food Insecurity among Subsistence-Oriented Indigenous Communities in Amazonia: a Qualitative Examination of Coping Strategies among Riverine Communities along the Caquetá River, Colombia - Torres Vitolas, Carlos A.; Harvey, Celia A.; Cruz García, Gisella S.; Vanegas Cubillos, Martha Cristina; Schreckenberg, Kate (Springer, 2019)
Despite the Amazon’s natural wealth, food insecurity is a major concern among indigenous communities. Yet, little is known about the socio-ecological dynamics shaping the contributions of local ecosystems to food security. In this study we examine how ecological features interact with normative structures, lifestyles, and livelihoods to expose indigenous peoples to food shortages and how they attempt to cope with worsening food insecurity conditions through participatory exercises with ten indigenous communities along the Caquetá River, Colombia. Our results indicate that traditional food systems are sensitive to human and natural capital disruptions. However, severe food insecurity is prevented by the combination of a well-preserved environment and traditional social institutions, which facilitates widespread access to wild foods, farmland, environmental knowledge, supportive relations, and labour. Nevertheless, traditional adaptations appear insufficient when food insecurity results from health shocks. Our findings highlight the need for interventions that pursue conservation objectives whilst promoting social structures supporting resilience.